Differing Effect of an EMG Biofeedback-Monitored Exercise Compared to an Un-monitored One in Vastus Medialis Obliquus and Vastus Lateralis Muscles Amplitude in Knee Osteoarthritis - Umi Syayyirotin A; Lukitra Wardhani; Fatchur Rochman (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives: The objective of the study was to know the difference of maximum and ratio amplitudes of vastus medialis obliquus and vastus lateralis muscles before and after exercise with and without EMG biofeedback monitoring in knee osteoarthritis patients.Methods: Randomized clinical study design. This study was conducted in Department of Physical Medicine and Rehabilitation Airlangga University, Dr. Soetomo hospital Surabaya. Twenty eight patients with knee osteoarthritis were randomly placed into 2 groups, the first group received progressive resistive exercise with EMG biofeedback, while the other group received training with progressive resistive method only. The ratio and maximum amplitudes of vastus medialis obliquus and vastus lateralis muscles were analyzed before and after 8 weeks exercise.Results: The amplitudes of vastus medialis obliquus and vastus lateralis were improved significantly in group receiving progressive resistive training method with EMG biofeedback monitoring (p=.01 and p=.001, respectively). Comparison between two groups after 8 weeks of progressive resistive exercise showed significant improvements on amplitude of vastus medialis obliquus muscle (p=.014) and amplitude ratio of VMO/VL (p=.034) in EMG biofeedback monitoring group.Conclusions: Progressive resistive exercise with EMG biofeedback monitoring could improvesignificantly the amplitudes of vastus medialis obliquus and vastus lateralis muscles and amplitude ratio of VMO/VL in knee osteoarthritis patients.Keywords: knee osteoarthritis, progressive resistive exercise, EMG biofeedback monitoring.